Tahap kesediaan staf kumpulan professional dan pengurusan terhadap mentoring - Chua, Sok Kheng. (Universiti Malaysia Sarawak (UNIMAS), 2002)
This study was aimed to identify professional and management staffs level of readiness towards mentoring. The study was done at Public Work Department, Sarawak Headquarters. 45 respondents were picked to be the sample of the study. The instrument used to collect feedback in this study was a designed questionaire regarding this field of study. The findings of this study was analyzed using Statistical Package for Social Sciences version 10.0 (SPSS 10.0). In this study, two statistical methods were used in which was descriptive aDd inferencial statistic. Mann-Whitney test was used to determine the differences between gender and level of readiness towards mentoring. Meanwhile, Pearson Correlation test was used to determine the relationship between purpose in mentoring and level of readiness towards mentoring, needed personality of mentor and level of readiness towards mentoring, functions of mentoring and level of readiness towards mentoring and lastly, approaches in mentoring and level of readiness towards mentoring. Pearson Correlation test gave a value of r = 0.523, p <0.05 when determining the relationship between purpose in mentoring and the level of readiness towards mentoring. This showed that there is a positive relationship between the two variables. Meanwhile Pearson Correlation test gave a value of r = 0.082, p>0.05 when determining the relationship between functions of mentoring and level of readiness towards mentoring and a value of r = 0.150, p>0.05 when determining the relationship between approaches in mentoring and level of readiness towards mentoring. These shows that both hypotheses null fails to be rejected. For the next hypotheses that stated that the more positive the personality of mentor the higher level of readiness towards mentoring is achieved, the findings showed that the hypotheses null is rejected. Finally, the findings of this study also found that the level of readiness towards mentoring in PWD, Sarawak Headquarters was at medium and high level. Several suggestions were proposed in this study to the benefits of the management and future researchers. Among the recommendations to the organization were to quickly implement the mentoring program, more explaination to the employees on mentoring, get consultation on planning and also observation on the mentoring program. Among recommendations for further researches were to broaden the scope of the sample and in different organization and research on the impact of mentoring on organization.